Transfer of Plasmid-Borne Beta-Lactamase in Neisseria gonorrhoeae - Baron, Ellen S. (1977)
Neisseria gonorrhoeae strain GC82 contains a plasmid specifying a β-lactamase (β-Lam(+)). Mixed incubation of strain GC82 with a penicillin-susceptible (β-Lam(−)), streptomycin-resistant mutant of strain GC9 results in the expression of β-lactamase activity and streptomycin resistance in the transcipients. The frequency of transfer of the plasmid-specified resistance to penicillin seems to be proportional to the initial input ratio of the mating mixture of donor to recipient and to correlate positively with bacterial density. Cell-to-cell transmission of the deoxyribonucleic acid (DNA) appears to be by a conjugal mechanism or, alternatively, by an as yet undescribed transducing phage. Additionally, whole-cell DNA from a β-lactamase-producing strain could be used to transform streptomycin-resistant recipients, resulting in the expression of both β-lactamase activity and streptomycin resistance in the transformants, and purified gonococcal plasmid DNA transformed Escherichia coli but not the gonococcus. Circular DNA extracted from donor GC82 comprised three molecular species (approximately 2.7, 4.8, and 25 megadaltons [Mdal]), whereas the recipients GC9-S (Str(r)) contained only the 2.7-Mdal cryptic DNA species. DNA from the GC9-S82 (Str(r), β-Lam(+)) transcipient contained a 4.8-Mdal species in addition to the cryptic molecular species (2.7 Mdal). The finding that the transcipient will not retransfer β-lactamase is consistent with the hypothesis that the 25-Mdal plasmid promotes mobilization of the smaller 4.8-Mdal R plasmid.